Chronic cavitary pneumonia by Rhodococcus equi in a highly prevalent tuberculosis country: a diagnosis challenge - Vechi, Hareton Teixeira; Oliveira, Eduardo Teodoro Gurgel de; Freitas, Marise Reis de; Rossi, Flávia; Britto, Maria Helena Marques Fonseca de; Alves, Manoella do Monte (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Rhodococcus equi is a facultative aerobic, intracellular, non-motile, non-spore-forming, Gram-positive, weakly acid-fast coccobacillus belonging to the group of nocardioform actinomycetes. R. equi infections are rare opportunistic illnesses in patients with Acquired Immunodeficiency Syndrome (AIDS), associated with a high mortality rate. The most common clinical presentation of R. equi infections is a chronic cavitary pneumonia. Due to its acid-fastness, R. equi can be mistaken for others acid-fast organisms, as Mycobacterium tuberculosis. In turn, R. equi is also a gram-positive pleomorphic bacteria and can be mistaken for diphtheroids or Micrococcus organisms, being accidentally disregarded as oral contaminants in sputum cultures. Therefore, in Brazil, a highly prevalent tuberculosis (TB) country, pulmonary infections caused by R. equi may mimic pulmonary TB and represent a diagnostic challenge. Here, we report on a case of chronic cavitary pneumonia by R. equi in a Human Immunodeficiency Virus (HIV)-infected patient, focusing on diagnostic aspects.